Active methodologies and their importance in child literacy process (Research, Society and Development, 2020)
This paper aims to identify the importance of the use of active methodologies in the process of literacy and literacy of children and the significant interventions of the teacher. The methodology with qualitative approach was anchored in Gil (2011) and for data collection interviews with semi-structured questions were used. The results pointed out that the main factor that stands out in the use of active methodologies is the transformation in the conception of learning, as it allows the student to think differently and helps in solving problems by connecting ideas that, in principle, seem disconnected. Therefore, it can be seen that the use of active methodologies by the teacher has provided noticeable changes in children's development. Despite being seen as a challenge for teachers, they realize that this practice further legitimizes the potential of teaching and contributes to a more complete formation of the child.